Adult testicular volume predicts spermatogenetic recovery after allogeneic HSCT in childhood and adolescence. Issue 6 (12th February 2014) - Wilhelmsson, Mari; Vatanen, Anu; Borgström, Birgit; Gustafsson, Britt; Taskinen, Mervi; Saarinen‐Pihkala, Ulla M.; Winiarski, Jacek; Jahnukainen, Kirsi
<x xml:space="preserve">Abstract</x> Background Testicular dysfunction and infertility are of major concern in long‐term survivors after allogeneic hematopoietic stem cell transplantation (HSCT). This study assesses predictive factors for very long‐term testicular recovery after allogeneic HSCT in childhood and adolescence. Procedure Testicular volume, sperm production and long‐term need of testosterone substitution were evaluated among 106 male survivors transplanted at Huddinge and Helsinki University Hospitals from 1978 through 2000, at a mean age of 8 ± 4.6 years (range 1–17). A mean ± SD of 13 ± 4.8 years (range 4–28) had elapsed since their HSCT and the mean age of the participants was 22 ± 6.0 years (range 12–42). An adult testicular volume was recorded in 74 patients at a mean age of 19 ± 3.3 years (range 14–36). Results Recipients conditioned with busulfan‐based regimens or regimens containing only cyclophosphamide had significantly larger adult testicular volumes (mean volume 18 ml and 16 ml vs. 9 ml, P < 0.00001, respectively) and lower serum levels of FSH (mean 9 IU and 5 IU vs. 19 IU, P < 0.01 and 0.001, respectively) compared to those conditioned with total body irradiation (TBI). Multivariate analysis demonstrated that a non‐leukemia diagnosis (P < 0.01) and adult testicular volume ≥15 ml (P < 0.03) positively impacted spermatogenetic recovery. Conclusions A larger adult testicular volume, normal serum levels of FSH and spermatozoa detected in a majority of seminal fluids after busulfan‐based or cyclophosphamide conditionings suggest very long‐term recovery of spermatogenesis after chemotherapy‐based regimens. A simple measurement of adult testicular volume may help predict spermatogenetic potential among pediatric HSCT survivors. Pediatr Blood Cancer 2014;61:1094–1100. © 2014 Wiley Periodicals, Inc.